The ritual of Khanduri Jeurat in Southwest Aceh, Indonesia - Abdul Manan; Nanda Ria (Proceedings of AICS - Social Sciences, 2017)
Khanduri jeurat is performed in each year in Kuta Tinggi, Southwest of Aceh. The local community performs the ritual by reading tahlil led by a teungku. The merit of praying is rewarded to the dead. This ritual has significant meaning for the community, which is held in the burial place of their family members. This research critically describes and analyzes the ritual of khanduri jeurat by using qualitative method applying descriptive approaches. The data collection was done by meticulous observation and in depth interview with the community leaders. The results showed that the ritual existing in the midst of the community was carried out annually with a series of stages and events such as organizing a meeting of gampong, cleaning graves, announcing the event, khanduri, ziarah, and closing speech. The purposes of this ritual are to alert the human towards the death, to show the form of honor of the community to the dead, and to create the togetherness and cohesiveness within the community. The ritual has several symbolic meanings. The Quranic recitation symbolizes the form of expecting Allah’s blessing. Tahlil symbolizes the form of the shared doa and gratitude. Khanduri bu reflects the togetherness and gratitude of the community. Ziarah represents the homage and love to dead. It also reminds someone to the death. This ritual has several benefits; reaffirming the local customs, reestablishing the camaraderie in the community, becoming as a cultural heritage, forming the togetherness and cohesiveness of the community, changing the behavior pattern to the better one, and reducing the potential for certain conflicts in the family and community.